ARAH BARU POLITIK KEWARGAAN ETNIS TIONGHOA DI INDONESIA (STUDI KASUS JAKARTA & MANADO) - Wasisto Raharjo Jati; Almunauwar Rusli; Rukmana Gonibala; Hendri Gunawan (Paradigma: Jurnal Kajian Budaya)
The new direction of ethnic Chinese citizenship politics in Indonesia is marked by a communal revival in non-governmental organizations, media and schools. The past of ethnic Chinese in Indonesia is indeed full of crises, but the future of Chinese citizens in Indonesia really depends on the policies of each ruling regime towards their group. The new direction of ethnic Chinese citizenship politics in Indonesia must be understood as a process of psychological rehabilitation for sentiment and antipathy towards China in the past. The interpretation of social reality and the social movements they carry out on a local scale should be appreciated and appreciated rationally and sympathetically. The government’s efforts to create democratic change require much greater effort. Perhaps with the development of democratization in Indonesia, residents of Chinese descent, es- pecially in Jakarta and Manado, will feel that there is security stability, economic growth and equal access to work so that social justice for all is truly achieved to the maximum. Thus, the central government needs to encourage the involvement of Chinese citizens in the world of local government politics at both the executive and legislative levels so that they can find the best way to deal with ethnic and religious tensions in our democratic political system